Trade Facilitation Measures under Free Trade Agreements: Are They Discriminatory against Non-Members? - Shintaro Hamanaka; Aiken Tafgar; Dorothea Lazaro (Asian Development Bank (ADB), 2010)
Are trade facilitation measures under free trade agreements (FTAs) discriminatory? This important question has yet to be sufficiently explored by the existing literature on trade facilitation. Despite the multilateral scope and non-discriminatory objectives of trade facilitation measures, some trade facilitation measures under FTAs can be discriminatory, similar to those in preferential tariff elimination. Based on a review of FTAs in Asia and the Pacific, this study provides detailed empirical analysis on whether or not trade facilitation provisions in FTAs are exclusive to contracting FTA partners and how the measures can be discriminatory against non-members.
hdl:11540/1947
Keywords: F13; F15; F42; F53; F59; 330; Trade facilitation; free trade agreements (FTAs); discriminatory measures; national treatment (NT); most-favored-nation (MFN)